Augmented Reality Media to Improve Concepts Understanding and Biomotor Skills - Darmawan, Gede Eka Budi; Parwati, Ni Nyoman; Warpala, I Wayan Sukra; Divayana, Dewa Gede Hendra (Jurnal Pedagogi dan Pembelajaran, 2024)
Students' biomotor skills are still in the low category and digital learning resources for traditional games are still minimal. The aim of this research is to analyze validity, practicality, test effectiveness, and analyze AR media user responses. This research is included in the type of development research. The subject of this research is the validity test of content experts, learning design experts, and media experts. The practical test involved 3 students at individual level and 12 students at small group level. User responses involved all experimental class students and teaching teachers. The experimental class involved 32 students and the control class consisted of 35 students. The data collection methods used were questionnaires and tests. Meanwhile, the data analysis method was carried out using qualitative descriptive analysis, quantitative descriptive analysis and inferential statistical analysis. The research results show that the validity of aspects of content, media, learning design, practicality and user response to AR media are in the very good category. Therefore, it is known that the novelty of AR media has a significant impact in increasing understanding of concepts and biomotor skills after controlling for students' initial knowledge. The implication of this research is that it can be used as a basis for developing 3-dimensional visualization to train students' biomotor skills.